Brexit and the future of UK fisheries governance: learning lessons from Iceland, Norway and the Faroe Islands. Issue 2 (3rd April 2019) - Huggins, Christopher; Connolly, John; McAngus, Craig; van der Zwet, Arno
ABSTRACT: Brexit presents significant challenges and uncertainties for the future governance of policy areas currently managed by the EU. This is especially the case with fisheries policy. The UK government has stated an ambition for post-Brexit fisheries policy to be based on sustainability and the use of scientific evidence. Yet how these aims will be achieved and formalised into post-Brexit governance structures remains to be seen. This article investigates fisheries governance arrangements in three non-EU countries: Iceland, Norway and the Faroe Islands. These cases offer lessons for the UK on governance and institutional arrangements for fisheries post-Brexit. However, none of these cases account for devolution and division of fisheries policy competences across multiple territories. This places significant limits on the potential for direct policy transfer from these countries to the UK.